LIFE SKILLS EDUCATION (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Kapil Sibal, Minister of HRD, emphasized that life skills should become the central focus of education. In this context, he said, “In the present day context, it is not enough for teachers to merely give information and knowledge to students ...human beings need wisdom. They need character. Life skills must become a central focus of educational efforts